Students´ Engagement In Schools: Differentiation and Promotion - Melo, Madalena (2013)
The objective of this work is to present elements of the project Student engagement in Schools (SES). The team consists of 10 researchers from six Universities. Student engagement in schools is a multidimensional construct that unites affective, behavioural, and cognitive dimensions of student adaptation in the school and has influence on students‘outcomes. The team of researchers conceptualized two major studies, a differential study to analyze the relations between SES and contextual factors, personal factors, student’s outcomes, and a quasi-experimental study to analyze the effects on SES of a specific intervention programmes. In study 1, the sample size is around 600 students (150 6th graders, 150 7th graders, 150 9th graders, and 150 10th graders). We shall focus on years of school transition, with rural and urban populations, on different regions of the country, and on students with different family background. We shall conduct questionnaires with national and international scales. The study 2 will involve students in 7th and 9th grade, from four classes, two of the experimental group and two of the control group. Patterns of verbal communications between a teacher and students can influence the classroom environment and SES. This model of communication would result in more effective student management and more time on-task for learning.